Analisis Penerapan Sistem E-loan Dan Prosedur Pemberian Kredit Kepemilikan Rumah (KPR) Dengan Metode Studi Kolerasional - Barus, Rini Afriani; Elsera, Marina; Hadinata, Edrian (Ali Institute of Research and Publication, 2023)
The E-Loan system at Bank BTN is an internal system used in credit processing with PPDPP's SiKasep platform which is a big data system for the availability of subsidized property and a verification application for Low-Income Communities (MBR) who are entitled to housing subsidies and succeeded in the SiKasep registration process. and get a subsidized mortgage program from Bank BTN. Subsidized Home Ownership Loans (KPR) are loans offered by banks and are also part of a government program in collaboration with the Ministry of Public Works. This study aims to determine the closeness and suitability of the application of the E-Loan System and the Procedure for Providing Subsidized Home Ownership Credit (KPR) at PT. State Savings Bank. The research method used is a correlational study. This study resulted in a measurement of the closeness and suitability of the E-Loan System and Procedures for Providing Home Ownership Loans (KPR) through a questionnaire.